Characterization of microplastic litter in the gastrointestinal tract of Solea solea from the Adriatic Sea. (March 2018) - Pellini, G.; Gomiero, A.; Fortibuoni, T.; Ferrà, Carmen; Grati, F.; Tassetti, A.N.; Polidori, P.; Fabi, G.; Scarcella, G.
Abstract: Micro-plastic particles in the world's oceans represent a serious threat to both human health and marine ecosystems. Once released into the aquatic environment plastic litter is broken down to smaller pieces through photo-degradation and the physical actions of waves, wind, etc. The resulting particles may become so small that they are readily taken up by fish, crustaceans and mollusks. There is mounting evidence for the uptake of plastic particles by marine organisms that form part of the human food chain and this is driving urgent calls for further and deeper investigations into this pollution issue. The present study aimed at investigating for the first time the occurrence, amount, typology of microplastic litter in the gastrointestinal tract of Solea solea and its spatial distribution in the northern and central Adriatic Sea. This benthic flatfish was selected as it is a species of high commercial interest within the FAO GFCM (General Fisheries Commission for the Mediterranean) area 37 (Mediterranean and Black Sea) where around 15% of the overall global Solea solea production originates. The digestive tract contents of 533 individuals collected in fall during 2014 and 2015 from 60 sampling sites were examined for microplastics. These were recorded in 95% of sampled fish, with more than one microplastic item found in around 80% of the examined specimens. The most commonly found polymers were polyvinyl chloride, polypropylene, polyethylene, polyester, and polyamide, 72% as fragments and 28% as fibers. The mean number of ingested microplastics was 1.73 ± 0.05 items per fish in 2014 and 1.64 ± 0.1 in 2015. PVC and PA showed the highest densities in the northern Adriatic Sea, both inshore and off-shore while PE, PP and PET were more concentrated in coastal areas with the highest values offshore from the port of Rimini. Graphical abstract: Highlights: The characterization of microplastics in the stomach of common sole is investigated. Investigations were oriented toward size and polymer composition. The majority of plastics were fragments, only a limited amount of fibers was scored. Abstract : Occurrence and polymeric composition of microplastics in stomach content of wild S. solea is assessed. Spatial distribution is more influenced both by polymers chemical-physical properties and peculiarities in the oceanographic conditions rather than by the feeding strategy of the species.